(untitled) (Medical Forum Monthly, 2021)
Objective: The study aimed to determine the effectiveness of high dose statin after four weeks of therapy among patients with acute coronary syndrome (ACS) presenting to a tertiary care hospital. Study Design: Cross-sectional study. Place and Duration of Study: This study was conducted at the Department of Cardiology, Ch. Pervaiz Elahi Institute of Cardiology in Multan and Jinnah Hospital in Lahore, from January 2020 to July 2020. Materials and Methods: About 160 ACS patients fulfilling the inclusion criteria were enrolled. All patients underwent a fasting serum lipid profile for measuring the serum low-density lipoprotein (LDL) level on the baseline. Then at the end of four weeks after obtaining treatment with high dose statin. The patients were treated with Rosuvastatin (40 mg) orally once daily and Atorvastatin (80 mg) on an alternate basis for four weeks. The effectiveness of high dose statins in lowering the serum LDL levels was measured. Results: The mean age of the enrolled patients was 41.88 ± 11.05 years, and more female patients presented at the study site during this period. The minimum serum LDL level observed after treatment was 103 mg/dl, and the mean hemoglobin level was 121.95 ± 11.83 mg/dl, where it maximally reached 140 mg/dl. 51.2% of patients were hypertensive, and the high-dose of statins effectively reduced the serum LDL levels among 71% of cases. It was found that the efficacy was significantly associated with the age, gender and presence of hypertension (p<0.05). Conclusion: The administration of the high dose of statins for four weeks (Rosuvastatin + Atorvastatin) effectively lowered the serum LDL levels among the ACS patients.